Management Whitepaper: The Introduction and Application of Sports Analytics in Professional Sport Organizations: A Case Study of the Tampa Bay Lightning - Michael Mondello; Christopher Kamke (Journal of Applied Sports Management, 2014)
Research Problem The purpose of this paper is to share best practices of how one professional sports organization, the Tampa Bay Lightning, has successfully integrated analytics within several departments to help management make business-related decisions. This paper introduces and applies a timely topic impacting professional sport organizations—sports analytics. Although analytics have been used for player personnel decisions related to paying, acquiring, and retaining talent, teams have also begun using analytics as a tool to assist with ticket pricing, product demand, scheduling, sponsorship ROI, Customer Relationship Management (CRM), and other financial/managerial applications. Therefore, this paper would likely be useful to stakeholders working in various segments of collegiate or professional sport organizations. In addition, the article would have added value to employees working in other types of sport settings including but not limited to: Associations (PGA, WTA), Leagues (NBA, MLB), or consulting groups. Sport managers involved with revenue generation may also find this article useful.